(untitled) (Actualité en allergologie et en immunologie au Canada, 2024)
Adenotonsillar hypertrophy (ATH) is a common pediatric condition marked by the growth of lymphoid tissues within the Waldeyer’s ring, which includes adenoids, palatine tonsils, and lingual tonsils. These tissues surround the upper airway and food passage, and play an immunological role, enlarging until about age 12, before gradually reducing during adolescence and adulthood. Untreated or poorly managed ATH can severely impact multiple health aspects of children. It is the primary cause of upper airway obstruction and obstructive sleep apnea (OSA) syndrome in children, which disrupts sleep and can severely impair cognitive development, school performance and behaviour. Chronic mouth breathing from ATH can alter dental arches and facial growth, known as adenoid facies. More severe outcomes include increased pulmonary pressures and the potential development of pulmonary hypertension and cor pulmonale due to chronic hypoxia and CO2 retention. As a result, tonsillectomy, with or without adenoidectomy (T&A), has become one of the most frequently performed surgeries in North America, with over 530,000 operations performed annually on children under age 15. This paper discusses the significant impact of ATH on pediatric health and the frequent need for surgical intervention. It covers the immunophysiology, influence of atopy, community-based assessments prior to specialist referrals, and an overview of available medical and surgical treatment options. Additionally, it outlines general indications for referring patients to otolaryngology.